2018
DOI: 10.12692/ijb/12.4.223-240
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal in drinking water its effect on human health and its treatment techniques – a review

Abstract: In human life, the dispute related to drinking water pollution is increasing day by day. In this article we discussed the contamination of drinking water with heavy metals. Heavy metals are a metallic element that has a relatively high density, specific gravity, or atomic weight and has toxic effects. Generally, humans are more likely to be exposed to heavy metals through water consumption and thus bioaccumulation of toxic metals takes place in the human body. Which causes serious human health hazards and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Cadmium level varies from 0.0014 to 0.0049 mg/L in four locations (25% of the samples analyzed), which are above the WHO maximum admissible limit of Cd in drinking water (0.003 mg/L) [15], but all the samples analyzed were found to comply the maximum admissible limits (0.005 mg/L) for Yemeni specifications [16] (Tables 3&4). Cadmium is a natural element in the earth's crust. An acute exposure to significantly higher cadmium levels can lead to a variety of negative health effects including Diarrhea, Vomiting, fever, lungs damage, muscle pain [17,18].…”
Section: Cadmium (Cd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cadmium level varies from 0.0014 to 0.0049 mg/L in four locations (25% of the samples analyzed), which are above the WHO maximum admissible limit of Cd in drinking water (0.003 mg/L) [15], but all the samples analyzed were found to comply the maximum admissible limits (0.005 mg/L) for Yemeni specifications [16] (Tables 3&4). Cadmium is a natural element in the earth's crust. An acute exposure to significantly higher cadmium levels can lead to a variety of negative health effects including Diarrhea, Vomiting, fever, lungs damage, muscle pain [17,18].…”
Section: Cadmium (Cd)mentioning
confidence: 99%
“…Manganese occurs naturally in many food sources, and the greatest exposure to manganese is usually from food [15]. Manganese is a mineral that naturally occurs in rocks and soil, but human activities are much responsible for underground water pollution by this element [17].There are some places in study area where the concentration of manganese found higher than the WHO allowed limit (0.4mg/L) [15].…”
Section: Manganese (Mn)mentioning
confidence: 99%
“…Furthermore, to enable cost-effective electrode material selection and electrode replacement planning, the rate of electrode material consumption must be understood. Into the bargain, high levels of metal content in drinking water have been linked to the development of illnesses such as skin irritations, digestive problems, and cancers [16]. Therefore, the metal content in the effluent must be determined to identify appropriate methods for treatment and safe disposal of the effluent.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of contaminated water affects the health of approximately 1.8 billion people all over the world. Bioaccumulation of non-degradable contaminants has aggravated the intensity and propensity of fatal diseases (Jamshaid et al, 2018). Potability of water is decided by the physicochemical and biological parameters according to World Health Organization (WHO) (Galal-Gorchev, 1993;Van Leeuwen, 2000), Environment Protection Agency (EPA) (Oberdiek, 2007), Environment Quality Standard (EQS) (Gobelius et al, 2018).…”
Section: Introductionmentioning
confidence: 99%